1-Octanol, a self-inhibitor of spore germination in Penicillium camemberti. (August 2016) - Gillot, Guillaume; Decourcelle, Nicolas; Dauer, Gaëlle; Barbier, Georges; Coton, Emmanuel; Delmail, David; Mounier, Jérôme
Abstract: Penicillium camemberti is a technologically relevant fungus used to manufacture mold-ripened cheeses. This fungal species produces many volatile organic compounds (VOCs) including ammonia, methyl-ketones, alcohols and esters. Although it is now well known that VOCs can act as signaling molecules, nothing is known about their involvement in P. camemberti lifecycle. In this study, spore germination was shown to be self-regulated by quorum sensing in P. camemberti . This phenomenon, also called "crowding effect", is population-dependent ( i.e. observed at high population densities). After determining the volatile nature of the compounds involved in this process, 1-octanol was identified as the main compound produced at high-spore density using GC-MS. Its inhibitory effect was confirmed in vitro and 3 mM 1-octanol totally inhibited spore germination while 100 μM only transiently inhibited spore germination. This is the first time that self-inhibition of spore germination is demonstrated in P. camemberti. The obtained results provide interesting perspectives for better control of mold-ripened cheese processes. Highlights: Spore germination in Penicillium camemberti is self-regulated by quorum sensing. Quorum sensing is observed when spore densities are high. Compounds involved in quorum sensing are volatile. 1-octanol was found to be the main volatile compound produced at high-spore density.